2010
DOI: 10.1590/s0100-40422010000400015
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal and phenolic compounds from Sidastrum paniculatum (L.) Fryxell and evaluation of cytotoxic and anti-inflammatory activities

Abstract: Recebido em 28/5/09; aceito em 17/11/09; publicado na web em 2/3/10Sidastrum paniculatum (L.) Fryxell belongs to the family Malvaceae and is popularly known as "malva roxa" or "malvavisco". The phytochemical study of the hexane, CHCl 3 and EtOAc phases from the crude ethanol extract of S. paniculatum led to the isolation of six compounds: a mixture of b-sitosterol and stigmasterol, 4-methoxy-3-hydroxybenzoic acid, 4-methoxy-3-hydroxybenzaldehyde, N-trans-feruloyltyramine and kaempferol-3-O-b-D-(6''-E-p-coumaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
2
10
0
1
Order By: Relevance
“…The presence of one ethoxy group in compound 9 was reinforced by the signals at δ C 63.51 (CH 2 , C-1′′) and δ C 15.42 (CH 3 , C-2′′). The 13 C-NMR spectrum confirmed the presence of two aromatic rings, with δ C 128.07 (C-2′/6′), δ C 115.34 (C-3′/5′) of one AA′BB′ system and δ C 110.9 (C-2), δ C 115.83 (C-5) and δ C 121.82 (C-6) of the AMX system, showing one methoxy group at δ C 55.75 (H 3 CO–C-3) [32,34].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of one ethoxy group in compound 9 was reinforced by the signals at δ C 63.51 (CH 2 , C-1′′) and δ C 15.42 (CH 3 , C-2′′). The 13 C-NMR spectrum confirmed the presence of two aromatic rings, with δ C 128.07 (C-2′/6′), δ C 115.34 (C-3′/5′) of one AA′BB′ system and δ C 110.9 (C-2), δ C 115.83 (C-5) and δ C 121.82 (C-6) of the AMX system, showing one methoxy group at δ C 55.75 (H 3 CO–C-3) [32,34].…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids are polyphenolic compounds with low molecular mass, found in leguminous, fruits, flowers, and leaves [ 39 ], having several biological activities, for example, anti-inflammatory [ 40 , 41 ] and antioxidant action [ 42 ]. Some flavonoids isolated from Malvaceae species [ 43 , 44 ], were: 3,7,3′,4′-tetrahydroxyflavone (quercetin); 5,7-dihydroxy-4′-methoxyflavone (acacetin); 7,4′-di-O-methyl-isoscutellarein; 5,8-dihydroxy-7,4′-dimethoxyflavone; 5,4′-dihydroxy-7-methoxyflavone (genkwanin) [ 22 ]; 5,4′-dihydroxy-3,7-3′-trimethoxyflavone (pachypodol); luteolin 7-O-β-D-glucopyranoside (cinaroside), 5,7,4′ trihydroxyflavone (apigenin); 5,7,3′,4′-tetrahydroxyflavone (luteolin) [F]; kaempferol-3-O-β-D-(6′′- E - p -coumaroyl)glucopyranoside (tiliroside) [ 21 , 22 , 23 , 45 , 46 , 47 ] and kaempferol 3,7-di-O-α- L -rhamnoside (lespedin).…”
Section: Resultsmentioning
confidence: 99%
“…Previous phytochemical studies of Sidastrum have reported the presence of steroids, triterpenes, and phenolic compounds (Cavalcante et al, 2010;Teles et al, 2015). We previously reported the isolation from S. micranthum of tiliroside, 4'-methoxy-5,7-dihydroxyflavone (acacetin), and 7,4′-di-O-methylisoscutellarein, as well as other phenolic compounds (Gomes et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…In recent decades, the emergence of microbial resistance to antibiotics has increased interest in exploring the potential of plant-derived antimicrobials (Silva et al, 2010). To increase our knowledge of S. micranthum phytoconstituents, this species was submitted to a phytochemical investigation.…”
Section: Introductionmentioning
confidence: 99%